NOT EVERY CRIME IS CRIMINAL ACT - Irfan Ardiansyah; Duwi Handoko; Rustam Rustam (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
If I say that crime is may be prosecuted by the state and is punishable by law. Is it possible to commit a sin can be punished by state law? For simple example is lie. Lies can be threatened with punishment because it is one form of crime (fraud). Lies cannot be threatened as well as punishments in criminal law because they are breach of contract (defaults). Even though within of criminal law,